Can policy forums overcome echo chamber effects by enabling policy learning? Evidence from the Irish climate change policy network. (22nd October 2018) - Wagner, Paul M.; Ylä-Anttila, Tuomas
Abstract: Research has repeatedly shown that individuals and organisations tend to obtain information from others whose beliefs are similar to their own, forming "echo chambers" with their network ties. Echo chambers are potentially harmful for evidence-based policymaking as they can hinder policy learning and consensus building. Policy forums could help alleviate the effects of echo chambers if organisations with different views were to participate and to use the opportunities that forums provide to learn from those outside their networks. Applying exponential random graph models on survey data of the Irish climate change policy network, we find that policy actors do indeed tend to obtain policy advice from those whose beliefs are similar to their own. We also find that actors tend not to obtain policy advice from the those that they encounter at policy forums, suggesting forums are not enabling policy learning.